SIPA1 Enhances Aerobic Glycolysis Through HIF-2α Pathway to Promote Breast Cancer Metastasis - Yao, Chenguang; Weng, Jun; Feng, Lingyun; Zhang, Wanjun; Xu, Yan; Zhang, Peijing; Tanaka, Yoshimasa; Su, Li (Frontiers in Cell and Developmental Biology, 2022)
Increased dependence on aerobic glycolysis is characteristic of most cancer cells, whereas the mechanism underlying the promotion of aerobic glycolysis in metastatic breast cancer cells under ambient oxygen has not been well understood. Here, we demonstrated that aberrant expression of signal-induced proliferation-associated 1 (SIPA1) enhanced aerobic glycolysis and altered the ATP production source from oxidative phosphorylation to glycolysis in breast cancer cells. We revealed that SIPA1 promoted the transcription of EPAS1, which is known as the gene encoding hypoxia-inducible factor-2α (HIF-2α), and then upregulated the expression of multiple glycolysis-related genes to increase aerobic glycolysis. We then found that blocking aerobic glycolysis by either knocking down SIPA1 expression or oxamate treatment led to the suppression of tumor metastasis of breast cancer cells in vitro and in vivo. Taken together, aberrant expression of SIPA1 resulted in the alteration of glucose metabolism from oxidative phosphorylation to aerobic glycolysis even at ambient oxygen levels, which might aggravate the malignancy of breast cancer cells. The present findings indicate a potential target for the development of therapeutics against breast cancers with dysregulated SIPA1 expression.